The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11239-021-02427-1
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASc score and modified CHA2DS2-VASc score can predict mortality and intensive care unit hospitalization in COVID-19 patients

Abstract: In this study, we investigated whether the CHA2DS2-VASc score could be used to estimate the need for hospitalization in the intensive care unit (ICU), the length of stay in the ICU, and mortality in patients with COVID-19. Patients admitted to Merkezefendi State Hospital because of COVID-19 diagnosis confirmed by RNA detection of virus by using polymerase chain reaction between March 24, 2020 and July 6, 2020, were screened retrospectively. The CHA2DS2-VASc and modified CHA2DS2-VASc score of all patients was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…Recently, Gunduz et al also showed the predictive value of the M-CHA2DS2-VASc score for ICU admission. 16 Consistent with these results, we demonstrated that the M-CHA2DS2-VASc score was an independent predictor of mortality in COVID-19 patients (OR: 1.406, 95% IC 1.096 -1.805, p = 0.007). In our cohort, COVID-19 patient non-survivors had significantly higher M-CHA2DS2-VASc [4 (IQR 3 -5) vs 2 (IQR 1 -4), respectively, p < 0.001] compared to survivors.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, Gunduz et al also showed the predictive value of the M-CHA2DS2-VASc score for ICU admission. 16 Consistent with these results, we demonstrated that the M-CHA2DS2-VASc score was an independent predictor of mortality in COVID-19 patients (OR: 1.406, 95% IC 1.096 -1.805, p = 0.007). In our cohort, COVID-19 patient non-survivors had significantly higher M-CHA2DS2-VASc [4 (IQR 3 -5) vs 2 (IQR 1 -4), respectively, p < 0.001] compared to survivors.…”
Section: Discussionsupporting
confidence: 87%
“…The final model was compared with two available models that have been externally validated in the general population: the CHA2DS2-VASc 19 and the clinical predictive model proposed by Wang et al 20 . The CHA2DS2-VASc is used to estimate thromboembolic stroke risk in atrial fibrillation and thrombotic risk in cardiac diseases and was evaluated in patients diagnosed with COVID-19.…”
Section: Methodsmentioning
confidence: 99%
“…Studies by Caetinkal 8 et al and Cicek 9 et al were found to have high risk of confounding factors as it was not clearly mentioned how the assessment was done. Study by Gunduz 10 et al was found to have high risk of attrition as control population follow up was not mentioned. Studies by Caro-codon 11 et al and Ruocco 12 et al scored low to moderate in various Risk of Bias domains.…”
Section: Resultsmentioning
confidence: 97%
“…The positive likelihood ratio was 2.8 (95% CI 2.0-4.0) and the negative likelihood ratio was 0.37 (95% CI 0.26-0.54). The diagnostic odds ratio (DOR) was 8 (95% CI [4][5][6][7][8][9][10][11][12][13][14][15]. The pooled AUC of CHA2DS2-VASc score for discriminating mortality was 0.80 (95% CI 0.76-0.83), indicating that it has high predicting accuracy (Figure 5).…”
Section: Predictive Value Of Cha2ds2-vasc Score On Mortalitymentioning
confidence: 99%